The Development Effectiveness of the Use of Doing Business Indicators, Fiscal Years 2010-20 - An Independent Evaluation - Independent Evaluation Group (Washington, DC: Independent Evaluation Group, 2022)
IEG began preparing the evaluation in June 2020, in response to a request from the World Bank Group Board’s Committee on Development Effectiveness. In March 2021, IEG produced an Issues Paper identifying lines of inquiry for the main evaluation, distributed it for internal and management reviews, and submitted it to CODE in June 2021. In September 2021, as the evaluation was undergoing final revisions, World Bank Group management decided to discontinue the Doing Business report. In announcing its decision, the Bank Group stated that it intended to work on a new approach to assess business and investment climates. In February 2022, the Bank published a pre-concept note introducing the Business Enabling Environment project (BEE), a new benchmarking exercise to “measure the business enabling environment in economies worldwide.” In this context and given the use of multiple other global indicators in reforms, the learning from this evaluation report is highly relevant. A cover note extends its findings to the use of other global indicators, including the successor Business Enabling Environment Project. The evaluation seeks to guide any new approach using evidence-based indicators so that it builds on the many good practices observed in Doing Business and considers the substantial power that these indicators have to motivate and engage client countries in business environment reform. It calls for indicators to be used in a balanced and accurate manner guiding the choice of reform priorities in client countries with the greatest development benefits for their socio-economic situation. The following generalized lessons can be drawn from the report: (i) Recognizing the powerful motivational effect of reform indicators, this evaluation notes the limitations in the coverage and guidance offered by any single indicator set on its own and advocates integrating them with complementary analytic tools and indicators. (ii) Recognizing the granularity and specificity of individual reforms in any given country context, the findings suggest that it is better to avoid using business regulatory or similar global indicators as explicit reform objectives or monitoring indicators in Bank Group projects and country strategies focused on improving the business environment. This does not preclude the use of primary data to track and measure agreed targets critical to Bank Group institutional commitments. (iii) Global indicators coverage and specifications are improved if, at regular and predictable intervals, they are updated to reflect learning from research and field experience to (i) improve links to important development outcomes; (ii) strengthen relevance to the experience of the subject of coverage; and (iii) adapt to technological changes in the areas covered by the indicators. (iv) The DB experience indicates the need for mechanisms and safeguards to assure the accuracy and validity of World Bank Group global indicator-based reports and related communications, using robust and transparent standards of evidence.